Ali Riaz on Bangladesh’s trials and tribulations - Hasan, Md. Mahmudul (Media New Age Limited, 2023)
People inside Bangladesh are muzzled by the fear of torture and in many cases have to choose between democracy and death. Others have opted for silence and tacit approval of the government’s corruption and oppressive policies in return for awards, positions, perks and privileges. Effective condemnation from the international community could make some positive change in the governance of Bangladesh. However, outside criticisms of the breakdown of democratic institutions in Bangladesh have been shrouded by strategic and economic motives, which helped the government remain in power through manufacturing fear in the hearts of people and through ‘coercive measures against its citizens’ including enforced disappearances. At a time when censorship and self-censorship typify much of the academic discussion of Bangladesh’s politics, Ali Riaz’s book provides a brave source of information about how the country has been ruled since early 2009. It is a must read for anyone — inside or outside Bangladesh — interested in the current affairs of the country.